Gut microbiota composition differences are associated with geographic location and age in malaria-endemic regions of Rwanda - Jean d’Amour Mutoni; Matthias Van Hul; Aline Uwimana; Camille Petitfils; Giselle C. Wong; Anthony Puel; Amandine Everard; Hélène Alexiou; Leon Mutesa; Jean-Paul Coutelier; Nadine Rujeni; Patrice D. Cani (PLoS ONE, 2025)
Evidence suggests that a significant interplay exists between the host gut microbiota and both the transmission and severity of malaria. Therefore, we explored the association between malaria and the gut microbiota across various geographic regions, considering host’s nutritional habits, helminth coinfections and age. This observational study was conducted in 3 malaria-endemic provinces of Rwanda: West, South and East. Demographic data, blood and fecal samples were collected from 169 participants (85 females and 84 males) aged between 2–78 years. We used questionnaire-derived qualitative data based on geographic regions, age, and nutrition. Malaria and soil-transmitted helminth diagnosis was assessed by microscopy. The gut microbial composition was analyzed based on bacterial 16S rRNA gene amplicon sequencing. We observed that preschool children had a significantly lower microbiota diversity compared to both school children (q = 0.027, K-Wallis) and adults (q = 0.011, K-Wallis). Unlike age, infection status (uninfected, malaria alone, soil-transmitted helminth alone or coinfection) was not significantly associated with the gut microbiota. However, using Bray-Curtis distances, we found a significantly differential gut microbial beta-diversity with a convergent distribution in the Western province compared to the other provinces (q = 0.0045, pairwise PERMANOVA). This geographic difference was not explained by any change in energy intake, protein, lipids, or carbohydrates consumption but was likely due to lower dietary fibre intake in the West compared to the South (q < 0.0001, ANOVA) and the East (q = 0.07, ANOVA). In conclusion, we have not found significant links between infection and gut microbiota. However, we showed a significant difference in the gut microbiota composition of people living in different geographic locations in Rwanda, possibly due to their nutritional habits.